Detection of Streptococcus equi subsp. equi in guttural pouch lavage samples using a loop‐mediated isothermal nucleic acid amplification microfluidic device - Ashley G. Boyle (Wiley, 2021)
Abstract Background Rapid point‐of‐care (POC) detection of Streptococcus equi subsp. equi (S. equi) would theoretically reduce the spread of strangles by identifying index and carrier horses. Hypothesis That the eqbE isothermal amplification (LAMP) assay, and the same eqbE LAMP assay tested in a microfluidic device format, are comparable to a triplex real‐time quantitative polymerase chain reaction (qPCR) assay that is commonly used in diagnostic labs. Samples Sixty‐eight guttural pouch lavage (GPL) specimens from horses recovering from strangles. Methods Guttural pouch lavage specimens were tested for S. equi retrospectively using the benchtop eqbE LAMP, the eqbE LAMP microfluidic device, and compared to the triplex qPCR, that detects 2 S. equi‐specific genes, eqbE and SEQ2190, as the reference standard using the receiver operating characteristic area under the curve (ROC). Results The 27/68 specimens were positive by benchtop eqbE LAMP, 31/64 by eqbE LAMP microfluidic device, and 12/67 by triplex qPCR. Using the triplex PCR as the reference, the benchtop eqbE LAMP showed excellent discrimination (ROC Area = 0.813, 95% confidence interval [CI] = 0.711‐0.915) as did the LAMP microfluidic device (ROC Area = 0.811, 95% CI = 0.529‐0.782). There was no significant difference between the benchtop LAMP and LAMP microfluidic device (ROC Area 0.813 ± 0.055 vs 0.811 ± 0.034, P = .97). Conclusions The eqbE LAMP microfluidic device detected S. equi in GPL specimens from convalescent horses. This assay shows potential for development as a POC device for rapid, sensitive, accurate, and cost‐efficient detection of S. equi.